2015
DOI: 10.1016/j.jstrokecerebrovasdis.2014.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Treatment Effect in the CHIMES Study

Abstract: Age, sex, baseline National Institutes of Health Stroke Scale score, and time to first dose are predictors of functional outcome in the CHIMES study. Stratification by prognosis showed that patients with 2 or more predictors of poorer outcome have better treatment effect with MLC601 than patients with single or no prognostic factor. These results have implications on designing future stroke trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…Recently, it has also been shown that transition from independence in activities of daily living to dependency between 3 and 12 months after a stroke is not insignificant [26]. A follow-up period of 3 months, as is the case in many acute stroke trials, may be of insufficient duration to demonstrate a treatment effect and may require strict patient selection as we have shown in our cohort [27,28]. Longer assessments after the initial short-course therapy may help in further evaluating stroke treatments, such as those using neuroprotectants, previously thought to be ineffective.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, it has also been shown that transition from independence in activities of daily living to dependency between 3 and 12 months after a stroke is not insignificant [26]. A follow-up period of 3 months, as is the case in many acute stroke trials, may be of insufficient duration to demonstrate a treatment effect and may require strict patient selection as we have shown in our cohort [27,28]. Longer assessments after the initial short-course therapy may help in further evaluating stroke treatments, such as those using neuroprotectants, previously thought to be ineffective.…”
Section: Discussionmentioning
confidence: 84%
“…We have identified several factors that predict poorer outcomes at 3 months, namely older age, female sex, worse baseline stroke severity and longer delay between stroke onset and initiation of treatment [6,8,9,10,15]. The same factors were reported in many in other previous studies [16,17,18,19,20,21,22] and were also found to predict deterioration at 1 and 5 years after a stroke [7,12,22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…It is thus important to understand the pattern of long-term recovery of subjects with stroke in a neurorestorative trial. In addition, we recently showed in the CHIMES study how predictors of functional outcome, such as age, sex, baseline National Institutes of Health Stroke Scale (NIHSS) score, and treatment delay, affect the ability of demonstrating treatment effect of a therapy for stroke recovery at 3 months [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in the Philippine cohort of the CHIMES trial, which included more patients with predictors of poorer prognosis, functional and neurological outcomes were improved in favor of MLC601 [15] . Stratification of the entire CHIMES cohort by prognosis also showed that patients with 2 or more predictors of poorer outcome have better treatment effect with MLC601 than patients with single or no prognostic factor [21] . A recent extension study of the CHIMES trial (CHIMES-E) revealed that a 3-month treatment with MLC601 after stroke improves the functional outcome for up to 2 years among patients with cerebral infarction of intermediate severity [22] .…”
Section: Introductionmentioning
confidence: 91%